2021
DOI: 10.28918/ijibec.v5i1.3675
|View full text |Cite
|
Sign up to set email alerts
|

The Intention of Millennial Generation in Paying Zakat through Digital Payments

Abstract: The zakat management organization (OPZ) is currently making innovations following technological developments, making it easier to pay zakat through digital payments. One of the groups of people who use digital payments is the millennial generation. The millennial generation is also known as the generation that likes things that are easy and related to technology. This study aims to analyze how the millennial generation intends to pay for zakat through digital payments. The method used in this research is logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
(18 reference statements)
0
6
1
Order By: Relevance
“…Even some studies show that many Muslims avoid the obligation to pay zakat (Abdullah & Sapiei, 2018;Andam & Osman, 2019). Even with a Muslim population of more than 229 million, Indonesia certainly has a relatively large potential for millennial muzakki (Al Athar & Al Arif, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even some studies show that many Muslims avoid the obligation to pay zakat (Abdullah & Sapiei, 2018;Andam & Osman, 2019). Even with a Muslim population of more than 229 million, Indonesia certainly has a relatively large potential for millennial muzakki (Al Athar & Al Arif, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The millennial generation also has excellent potential to give alms, infaq and waqf (Al Athar & Al Arif, 2021). Charities Aid Foundation (2021) states that in 2020, Indonesia will become the first country on the list of the most generous in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous research that has been done supports this statement. Athar & Arif (2021) stated in their research that trust influences the intention of the millennial generation in making zakat payments through digital payments. Amofah & Chai (2022) also showed that trust positively mediates the relationship between performance expectancy and intention in using technology.…”
Section: Trustmentioning
confidence: 99%
“…With 87.20 percent of the Indonesian population being Muslim and the millennial generation growing in 2020, the potential for ZISWAF is substantial. This information poses a difficulty for zakat collecting entities (M. D. Al Athar & Al Arif, 2021). Given this context, it is intriguing to examine ZISWAF through the lens of fintech among the millennial age, given Indonesia's immense potential.…”
Section: Introductionmentioning
confidence: 99%